How do leaf wetting events affect gas exchange and leaf lifespan of plants from seasonally dry tropical vegetation?. (26th July 2019) - Holanda, A. E. R.; Souza, B. C.; Carvalho, E. C. D.; Oliveira, R. S.; Martins, F. R.; Muniz, C. R.; Costa, R. C.; Soares, A. A.
Abstract: Foliar uptake of dew is likely an important mechanism of water acquisition for plants from tropical dry environments. However, there is still limited experimental evidence describing the anatomical pathways involved in this process and the effects of this water subsidy on the maintenance of gas exchange and leaf lifespan of species from seasonally dry tropical vegetation such as the Brazilian caatinga . We performed scanning electron, bright‐field and confocal microscopic analyses and used apoplastic tracers to examine the foliar water uptake (FWU) routes in four woody species with different foliar phenology and widely distributed in the caatinga . Leaves of plants subjected to water stress were exposed to dew simulation to evaluate the effects of the FWU on leaf water potentials, gas exchange and leaf lifespan. All species absorbed water through their leaf cuticles and/or peltate trichomes but FWU capacity differed among species. Leaf wetting by dew increased leaf lifespan duration up to 36 days compared to plants in the drought treatment. A positive effect on leaf gas exchange and new leaf production was only observed in the anisohydric and evergreen species. We showed that leaf wetting by dew is relevant for the physiology and leaf lifespan of plants from seasonally dry tropical vegetation, especially for evergreen species.